2021
DOI: 10.17267/2238-2704rpf.v11i1.3359
|View full text |Cite
|
Sign up to set email alerts
|

Estilo de vida e nível de atividade física de indivíduos portadores de miocardiopatia chagásica

Abstract: INTRODUÇÃO: A doença de Chagas (DC) constitui uma infecção parasitária causada pelo protozoário flagelado Tripanosoma cruzi. Estimativas apontam a existência de, aproximadamente, cinco milhões de indivíduos infectados, principalmente, na América Latina, com o Brasil datando entre 1,9 a 4,6 milhões de indivíduos sob o mesmo aspecto infeccioso. O desfecho cardíaco configura um dos aspectos mais importantes, com manifestações condizentes à disfunção ventricular sistólica ou diastólica, disfunção autonômica cardía… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
1
0
0
Order By: Relevance
“…The lifestyle of people living with chronic diseases, such as Chagas disease, is a point of need for discussion, given that these people often need to adjust various aspects of their daily lives when receiving this type of diagnosis. In this sense, the findings concerning the NANDA-I domains of this study reflect this concern, considering that it has already been observed that people with Chagas heart disease have low lifestyle scores in the areas of physical activity, sleep, safety, stress, and safe sex 21 .…”
Section: Discussionsupporting
confidence: 73%
“…The lifestyle of people living with chronic diseases, such as Chagas disease, is a point of need for discussion, given that these people often need to adjust various aspects of their daily lives when receiving this type of diagnosis. In this sense, the findings concerning the NANDA-I domains of this study reflect this concern, considering that it has already been observed that people with Chagas heart disease have low lifestyle scores in the areas of physical activity, sleep, safety, stress, and safe sex 21 .…”
Section: Discussionsupporting
confidence: 73%